PLACE AND ROLE OF SOFT TISSUE ULTRASOUND EXAMINATION IN TOURNIQUET SYNDROME - Lurin, I.A.; Khoroshun, E.M.; Nehoduiko, V.V.; Makarov, V.V.; Tertyshnyi, S.V.; Tiron, O.I.; Vastyanov, R.S. (World of Medicine and Biology, 2024)
The purpose of the study was to demonstrate and analyze the possibilities of ultrasound diagnosis of tourniquet syndrome. All wounded were admitted at the Military Medical Clinical Center of the Northern Region of the Command of the Medical Forces of the Armed Forces of Ukraine from advanced surgical groups at different times from the wound with an existing tourniquet on the limb at different times after the tourniquet was placed (from 5 to 72 hours, on average 8.2±0.6). There were 32 male wounded. The average age of the wounded was 39.4±2.6 years. According to the location of the tourniquet, the wounded are distributed as follows: shoulder – 5 (15.6 %), thigh – 24 (75 %), leg – 3 (9.4 %) patients. All the wounded underwent an ultrasound and elastographic examinations. We used an average result after 12 measurements of each muscle group. When studying the data of muscle elastography against the background of the existing tourniquet, a significant difference in the elastography indicators of healthy superficial and deep muscles being under the tourniquet due to compression is noted. Elastography indicators in deep muscles are always higher than in superficial muscles. Changes in muscle elastography are localized by the location of the tourniquet. The use of ultrasound examination of soft tissues in tourniquet syndrome has an additional character. According to the data of elastography of soft tissues in the case of tourniquet syndrome, it is possible to determine the extent of soft tissue damage, which is important for determining the size of surgical intervention.
Keywords: gunshot wounds of the limbs; tourniquet syndrome; soft tissue; elastography; ultrasound diagnostics